PEMBUATAN ARANG AKTIF DARI AMPAS TEBU DAN APLIKASINYA SEBAGAI ADSORBEN ZAT WARNA MERAH DARI LIMBAH PENCELUPAN BENANG TENUN SARUNG SAMARINDA - Ririn Ariyani (PROSIDING SEMINAR KIMIA, 2020)
The research about preparation of activated charcoal from bagasse and its application as an adsorbent for red dye from the waste weaving of the sarong in Samarinda has been conducted. Determination of the surface area of ​​charcoal before and after activation using the methylene blue method was 176.1918 m2/g and 180.2635 m2/g, respectively, characterization by FT-IR on activated charcoal before and after activat ion showed that there are C - H. aromatic, C = O, C = O and C - O, based on the XRD characterization results showed that after activation activated carbon there is an amorph peak with a heterogeneous surface which indicated that the characteristic carbon appeared in the area between 22.26-24.31o. Analysis of the quality of charcoal after activation obtained a moisture content of 5%; ash content 4.20% and volatile mater 29.44%. The use of activated charcoal for adsorption on the rhodamine B dye and the red dye from waste dyeing yarn weaving sarong Samarinda used a UV-Vis spectrophotometer with several variations of optimization, namely: optimum contact time variation, optimum adsorbent weight variation, optimum concentration variation and comparison of the optimum optimization results at time variations contact and adsorbent weight of rhodamine B dye and red dye from from waste dyeing yarn weaving sarong Samarinda, the results of the optimization comparison of optimum contact time obtained the highest degradation% in red dye from from waste dyeing yarn weaving sarong Samarinda, namely 66.410%, optimum at 45 minutes and the optimization of adsorbent weight variations obtained the highest The optimum red dye from from waste dyeing yarn weaving sarong Samarinda is 93.387% at a weight of 0,2 g. Keywords: Sugarcane Bagasse, Activated Charcoal, Adsorbent, from waste dyeing yarn weaving sarong Samarinda.